Leaking from the phase space of the Riemann–Liouville fractional standard map - Méndez-Bermúdez, J. A.; Peralta-Martinez, Kevin; Sigarreta, José M.; Leonel, Edson D. [UNESP] (Elsevier, 2023)
In this work we characterize the escape of orbits from the phase space of the Riemann–Liouville (RL) fractional standard map (fSM). The RL-fSM, given in action–angle variables, is derived from the equation of motion of the kicked rotor when the second order derivative is substituted by a RL derivative of fractional order α. Thus, the RL-fSM is parameterized by K and α∈(1,2] which control the strength of nonlinearity and the fractional order of the RL derivative, respectively. Indeed, for α=2 and given initial conditions, the RL-fSM reproduces Chirikov's standard map. By computing the survival probability PS(n) and the frequency of escape PE(n), for a hole of hight h placed in the action axis, we observe two scenarios: When the phase space is ergodic, both scattering functions are scale invariant with the typical escape time ntyp=exp〈lnn〉∝(h/K)2. In contrast, when the phase space is not ergodic, the scattering functions show a clear non-universal and parameter-dependent behavior.
Keywords: Classical scattering; Fractional standard map; Nonlinear dynamics